The Correlation Between Creatinine and Potassium Levels in Patients With Chronic Kidney Failure - Ni Made Putri Sumyarini; Putu Ayu Parwati; Diah Prihatiningsih (Jurnal Kesehatan Cendikia Jenius, 2025)
Chronic Kidney Disease is a progressive and irreversible decline in kidney function that affects the body’s ability to maintain fluid and electrolyte balance, including potassium. Creatinine is a primary indicator of decreased kidney function, while potassium plays a crucial role in maintaining proper muscle and cardiac function. A significant increase in potassium levels due to impaired kidney function can lead to cardiac arrhythmias, which may be fatal. Therefore, analyzing the relationship between these two parameters is essential for detecting the risk of complications and supporting the management of CKD patients. The purpose of this study was to determine the relationship between serum creatinine and potassium levels in patients with chronic kidney disease. This study used an observational analytic design with a cross-sectional approach. The sample consisted of 32 patients at Rumah Sakit Umum Bali Jimbaran who underwent simultaneous creatinine and potassium testing between March – Mei 2025. Data were analyzed using the Spearman correlation test. The results of this study is most patients had elevated creatinine levels (84.37%) and normal potassium levels (59.37%). The Spearman correlation test showed a significance value p = 0.046 and a correlation coefficient r = 0.356, indicating a positive correlation with weak strength between creatinine and potassium levels. The conclusion of this study is theres a statistically significant relationship between creatinine and potassium levels in patients with chronic kidney disease, although the strength of the correlation is weak.